2021
DOI: 10.3390/ijms22147678
|View full text |Cite
|
Sign up to set email alerts
|

A New N-Substituted 1H-Isoindole-1,3(2H)-Dione Derivative—Synthesis, Structure and Affinity for Cyclooxygenase Based on In Vitro Studies and Molecular Docking

Abstract: Isoindoline-1,3-dione derivatives constitute an important group of medicinal substances. In this study, nine new 1H-isoindole-1,3(2H)-dione derivatives and five potential pharmacophores were obtained in good yield (47.24–92.91%). The structure of the new imides was confirmed by the methods of elemental and spectral analysis: FT–IR, H NMR, and MS. Based on the obtained results of ESI–MS the probable path of the molecules decay and the hypothetical structure of the resulting pseudo-molecular ions have been propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…The binding of one molecule to a protein reduces the affinity for binding to another site in the protein. As previous studies have shown, the four phthalimide derivatives studied in this work show good anti-inflammatory properties [ 3 ]. The interaction with albumin of drugs with such an effect was studied by Mohammadnia [ 28 ].…”
Section: Resultssupporting
confidence: 52%
See 3 more Smart Citations
“…The binding of one molecule to a protein reduces the affinity for binding to another site in the protein. As previous studies have shown, the four phthalimide derivatives studied in this work show good anti-inflammatory properties [ 3 ]. The interaction with albumin of drugs with such an effect was studied by Mohammadnia [ 28 ].…”
Section: Resultssupporting
confidence: 52%
“…The synthesis of compounds analyzed was performed in the Department of Medicinal Chemistry, Wroclaw Medical University, and described in work [ 3 ]. Studied proteins, BSA, AAG, GG, and 0.01 M phosphate buffer tablets were bought from Sigma-Aldrich Chemie GmbH, (St. Louis, MO, USA).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Compounds F1-F4 fulfill the obtained in this study are consistent with the previously described properties of phthalimide derivatives. [22] As previously determined, the type of substituent in the benzene ring, its position (o, m, p) and the presence of the OH/C═O group, and the length of the alkyl linker have a significant influence on the affinity and selectivity of the compound towards the COX- Medical University. [9][10][11] The InChI codes of the investigated compounds, together with some biological activity data, are provided as Supporting Information.…”
Section: Antinociceptive Activitymentioning
confidence: 88%